RANCANG BANGUN PERBAIKAN FAKTOR DAYA SECARA OTOMATIS MENGGUNAKAN ARDUINO MENGGUNAKAN KAPASITOR AGAR TERJADINYA EFESIENSI PEMAKAIAN LISTRIK - Rizki Sentosa; Andi Syofian (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
Decreased power factor values due to the use of inductive equipment are not monitored. Because with a decrease in the power factor, both consumers and suppliers of electrical energy will suffer losses. For consumers, the disadvantages include that the system voltage will decrease, the supply of electric power will not be optimal. Factors that affect the decrease in power factor is the use of inductive loads. Based on Ministerial Regulation No. 07 of 2010, CHAPTER III Article 5 paragraph 3 which states that the power factor value that is subject to a penalty on electricity consumers is a power factor below 0.85 and the lowest is 0.62. And based on SPLN 70-1 the standard power factor (cos φ) is ≥ 0.85, if the power factor is less than 0.85 then PLN will take into account the excess use of Kilo Volt Ampere Reactive Hours (KVArH). Making a power factor improvement tool to meet predetermined power factor needs using the PZEM-004t sensor and Arduino as a control tool and the Node-Red application as an interface for displaying data reading values. To improve the power factor, capacitors are used which will be active when needed at the command of the Arduino control. From the experiments it was found that the efficiency occurred from 0.67% to 23% so that the use of the tool can provide benefits for consumers. Capacitor value for maximum power factor improvement is 425.12Var.